Stock Market Literacy, Trust, and Participation - Balloch, Adnan; Nicolae, Anamaria; Philip, Dennis (Review of Finance, 2015)
This article studies the importance of stock market literacy and trust for stock ownership decisions. We find that these two distinct channels simultaneously explain not only the probability of participation, but, conditional on participation, also explain the share of investment in stocks. Once we account for stock market literacy, sociability is no longer significant for participation; what matters is literacy rather than sociability. Further, we observe that economic shocks and future expectations are key behavioral characteristics that explain a household’s decision to invest in stocks. However, upon participation, a larger set of behavioral characteristics explains the level of stock investment.